Market Dynamics and Marketing Strategies of Agricultural Products in Enhancing the Competitiveness of Local Agribusiness - Jenneke Widya M. Maasi (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study explores the market dynamics, marketing strategies, and competitiveness of local agribusinesses, with a focus on understanding how these factors influence the success and sustainability of small-scale agricultural enterprises in a globalized market. Using a qualitative research approach, specifically a literature review methodology, the study synthesizes recent academic works, reports, and policy documents from 2015 to 2025 to identify key trends and challenges in the agricultural sector. The findings reveal that globalization, technological advancements, and shifting consumer preferences for sustainable, locally sourced products are reshaping the market dynamics in agriculture. Local agribusinesses face increasing competition from international producers, but they also have opportunities to differentiate themselves through branding, certification, and digital marketing strategies. Moreover, access to financial resources, market networks, and government support is critical to enhancing the competitiveness of local producers. The study highlights the importance of adopting innovative marketing strategies, improving production efficiency, and leveraging policy support to foster a more competitive and sustainable agribusiness sector. Based on these findings, the paper provides recommendations for future research, including exploring the role of digital transformation, the impact of public-private partnerships, and examining consumer behavior trends in relation to sustainability.